Effect of phycocyanin and phycoerythrin on antioxidant and antimicrobial activity of refrigerated low-fat yogurt and cream cheese - Azadeh Ahmadi; Seyed Amir Ali Anvar; Bahareh Nowruzi; Leila Golestan (Scientific Reports)
Abstract Cyanobacterial phycobiliproteins, such as phycoerythrin (PE) and phycocyanin (PC), are colored potential bioactive proteins that have antioxidant and antimicrobial properties. In this study, we formulated a new food prototype based on PE and PC-fortified low-fat yogurt and cream cheese. Four distinct low-fat yogurt and cream cheese products were manufactured, including a control group (No PE and PC), samples produced with phycoerythrin (+ PE), samples produced with phycocyanin (+ PC), and samples produced with both phycoerythrin and phycocyanin (PC + PE). Afterwards statistically compared the physicochemical composition, colorimetric properties, antioxidant and antimicrobial activities, and sensory profile of the fortified foods at 4 °C and 8 °C for 28 and 42 days. Additionally, we confirmed that PE and PC are not toxic to Caenorhabditis elegans at concentrations up to 1 mg/mL. The results showed that the MIC of PE and PC against E. coli was significantly higher than against S. aureus (3.12 ± 0.05 µg/mL vs. 1.56 ± 0.01 µg/mL, respectively; p ≤ 0.05). Additionally, the maximum diameter of the inhibition zone of PE and PC against S. aureus was significantly higher than against E. coli (6.6 ± 0.011 mm vs. 11.66 ± 0.02 mm, respectively; p ≤ 0.05). Results of color parameters showed that the control group had significantly higher L* values than the samples enriched with PE and PC. Moreover PE and PC significantly increased the a* and b* values respectively. The amount of ΔE in the control yogurts and cream cheese was higher than in the samples with PE and PC. Overall, the results showed that adding PE and PC had a significant effect on all measured factors (p < 0.01). Cream cheeses and low-fat yogurts enriched with either PE or PE + PC had the greatest antioxidant activity and the lowest number of psychrophilic bacteria and mold, and yeast counts at the end of the test period. Therefore, low-fat yogurt and cream cheese containing cyanobacterial PE and PC can be considered an innovative dairy product for the food industry. This study marks the initial effort to employ PE and PC derived from Nostoc sp. and Spirulina sp. as antioxidant and antimicrobial agents in the food industry.